An unusual cause of genu valgum and persistent instability - Holloway, Edward (J Surg Case Rep, 2017)
We present the case of a professional adolescent footballer who attended our clinic with ongoing instability symptoms and valgus knee deformity after conservative management of an medial collateral ligament injury. The patient was found to have sustained a contra-coup Salter Harris Type V injury to his lateral distal femur physis resulting in premature growth arrest and deformity. Salter Harris Type V injuries are rare, and often not diagnosed until growth has arrest has occurred due to lack of identifiable features on initial plain radiographs. The patient was successfully treated with opening wedge femoral osteotomy and plication of the medial collateral ligament. This case reinforces the need for awareness of such injuries to avoid delayed diagnosis and describes options for management.